Объяснение:
H2SO4 + Na2CO3 = Na2SO4 + CO2↑ + H2O
2H(+) + SO4(2-) + 2Na(+) + CO3(2-) = 2Na(+) + SO4(2-) + CO2↑ + H2O
2H(+) + CO3(2-) = CO2↑ + H2O
H2SO4 + 2KOH = K2SO4 + 2H2O
2H(+) + SO4(2-) + 2K(+) + 2OH(-) = 2K(+) + SO4(2-) + 2H2O
H(+) + OH(-) = H2O
H2SO4 + MgO = MgSO4 + H2O
2H(+) + SO4(2-) + MgO = Mg(2+) + SO4(2-) + H2O
2H(+) + MgO = Mg(2+) + H2O
H2SO4 + Fe = FeSO4 + H2
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Fe(0) -2e = Fe(+2) 1 ок-ие
в-ль
H2SO4 + Zn(OH)2 = ZnSO4 + 2H2O
2H(+) + SO4(2-) + Zn(OH)2 = Zn(2+) + SO4(2-) + 2H2O
2H(+) + Zn(OH)2 = Zn(2+) + 2H2O
1) P2O5 + 6NaOH = 2Na3PO4 + 3H20
Полное ионное: P2O5+ 6Na(+) + 6OH (-) = 6Na(+) + PO4(3-) + 3H2O
Краткое ионное: P2O5 + 6OH(-) = PO4(3-) + 3H2O
2) H2SO4 + 2NaOH = Na2SO4 + 2H2O
Полное ионное: 2H(+) + SO4(2-) + 2Na(+) + 2OH (-) = 2Na(+) + SO4(2-) + 2H2O
Краткое ионное: 2H(+) + 2OH(-) = 2H2O
H(+) + OH(-) = H2O
3) ZnCl2 + 2NaOH = Zn(OH)2 + 2NaCl
Полное ионное: Zn(2+) +2Cl(-) + 2Na(+) + 2OH(-) = Zn(OH)2 + 2Na(+) + 2Cl(-)
Краткое ионное: Zn(2+) + 2OH(-) = Zn(OH)2
4) Fe2(SO4)3 + 6NaOH = 2Fe(OH)3 + 3Na2SO4
Полное ионное: 2Fe(3+) + 3SO4(2-) + 6Na(+) + 6OH(-) = Fe(OH)3 + 6Na(+) + 3SO4(2-)
Краткое ионное: 2Fe(3+) + 6OH(-) = Fe(OH)3